Incidental Diagnosis of Carcinoma Prostate Of Turp Chips Done for Bph : A Study of Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Prostate cancer awareness is increasing day by day, especially in the USA and western world. Before PSA period, up to 27% of prostate cancers were detected incidentally in the TURP chips done for BPH. The Incidental diagnosis of prostate cancer in patients treated for BPH by a transurethral prostate resection is seen in 1.4-16.7% of patients, but it’s incidence is decreasing due to the use of Serum PSA testing. Nevertheless, some patients are still diagnosed with incidental prostate cancer. However, incidentally detected carcinoma prostate has been reported to vary across the globe since various factors can influence the identification of this malignancy in TURP specimens. In this study, we concentrated on rates of incidentally detected prostate cancer in TURP chips done for BPH in our hospital. Materials and methods: This retrospective study of histopathological findings of TURP chips was conducted for patients undergoing TURP from 2010. The inclusion criteria were patients diagnosed with BPH, DRE showing no abnormal hard areas and age adjusted PSA value is normal. Patients with elevated PSA, abnormal DRE, documented urinary tract infection and proved Adenocarcinoma Prostate (CaP) were excluded from the study. The age of the patients, clinical diagnosis, occurrence of carcinoma of prostate in the TURP chips and Gleason’s scores were recorded. Results: A total of 263 patients who fulfilled the inclusion criteria were studied. The incidence of CaP in the study group was 5.3 % (14/263). 10 (71.4 %) patients were aged ³65 years or older had maximum incidence of CaP. Conclusions: The rate of incidentally detected adenocarcinoma prostate in patients undergoing TURP for clinically diagnosed BPH was found to be only 5.3 % in our study, which is low when compared with similar studies done elsewhere in the world.JCMCTA 2017 ; 28 (2) : 16-20